MANAJEMEN STRATEGIK DALAM MENINGKATKAN MINAT CALON JEMAAH HAJI DAN UMROH PT. KRISMA TOUR KABUPATEN CIANJUR - Iwan Muhamad; Deny Muhamad (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Strategic management is the science and art involved in formulating, implementing, and evaluating cross-functional decisions that enable an organization to achieve its goals. Strategic management can help travel companies create additional value and differentiate from competitors. This can help companies attract the interest of potential pilgrims and also increase profits for the company. The formulation of the problem in this research is how to formulate strategies, implement strategies, and evaluate strategies in increasing the interest of prospective Hajj and Umrah pilgrims at PT. Krisma Tour. This research aims to determine strategy formulation, strategy implementation, and strategy evaluation in increasing the interest of prospective Hajj and Umrah pilgrims at PT. Krisma Tour. This research uses a descriptive qualitative approach. The data collection techniques used in this research are interviews with two sources, observation, and documentation studies related to strategic management that have been implemented by PT Krisma Tour. The results of this research reveal that strategy formulation in the company PT. Krisma Tour has carried out either alternative strategies or special strategies. The special strategy used is doing door-to-door or word of mouth and maximizing social media as digital marketing. Strategy implementation at PT. Krisma Tour still only covers around 95% of, the implementation of vision and mission, implementation of goals, organizational structure, and implementation of marketing strategies. The shortcomings of strategy implementation at PT Krisma Tour are still in the development process, such as developing employee quality through various types of training. Strategy evaluation at the PT Krisma Tour company is carried out regularly every 3 months, the sections or segments evaluated include employee performance and employee target achievements.